INNOVATIVE LEARNING MEDIA IN TEACHING 2D DRAWING MODIFICATION WITH CAD TECHNOLOGY - Selfia, Meliza; Hamdani, Aam; Komaro, Mumu (Universitas Pendidikan Indonesia, 2024)
The lack of understanding of students on 2D drawing modification material using CAD is the background for this research. The purpose of this study is to produce products in the form of video tutorial learning media, knowing the feasibility of experts, knowing user responses, and knowing the improvement of learning outcomes after using media. This study used quantitative research methods with a pre-experimental research design with the type of one group pre-test post-test design. Purposive sampling was conducted to select 34 samples from TPM grade XI learners. This research produces video tutorial learning media. The results of the feasibility assessment conducted by show that the video tutorial learning media that has been made is declared